2011
DOI: 10.1186/1476-4598-10-126
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and manipulation of docetaxel resistant prostate cancer cell lines

Abstract: BackgroundThere is no effective treatment strategy for advanced castration-resistant prostate cancer. Although Docetaxel (Taxotere®) represents the most active chemotherapeutic agent it only gives a modest survival advantage with most patients eventually progressing because of inherent or acquired drug resistance. The aims of this study were to further investigate the mechanisms of resistance to Docetaxel. Three Docetaxel resistant sub-lines were generated and confirmed to be resistant to the apoptotic and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(193 citation statements)
references
References 39 publications
(46 reference statements)
14
175
1
Order By: Relevance
“…ABCB1 belongs to the ATP-binding cassette transporters that use the energy of ATP hydrolysis to transport substrates across cell membranes, and ABCB1 overexpression results in diminished efficacy of anticancer drugs (30). Previous studies reported that increased ABCB1 conferred resistance to chemotherapeutic agents in several cancers (31)(32)(33). ABCB1 is also closely correlated with CSC-like properties and is one of the CSC markers (23).…”
Section: Discussionmentioning
confidence: 99%
“…ABCB1 belongs to the ATP-binding cassette transporters that use the energy of ATP hydrolysis to transport substrates across cell membranes, and ABCB1 overexpression results in diminished efficacy of anticancer drugs (30). Previous studies reported that increased ABCB1 conferred resistance to chemotherapeutic agents in several cancers (31)(32)(33). ABCB1 is also closely correlated with CSC-like properties and is one of the CSC markers (23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the increased survival observed in response to docetaxel under hyperglycaemic conditions with DU145 and LNCaP cells, we found that the response of PC3 cells to docetaxel under the same conditions was unaffected. One mechanism of resistance to docetaxel is caused by reduced drug accumulation within cells due to raised levels of proteins which promote efflux of the drug, such as the ATP-binding cassette transporter P-glycoprotein (P-gp;O'Neill et al 2011). It will be interesting to investigate whether IGFBP2 alters the sensitivity to docetaxel by affecting the levels or activity of P-gp.…”
Section: Discussionmentioning
confidence: 99%
“…Many AMCD-resistant tumors, including docetaxel-resistant prostate cancer cells, express low levels of the proapoptotic Bax protein and high levels of the antiapoptotic BCL-2 and BCL-XL proteins, thus generating resistance to therapy-induced apoptotic cell death (O'Neill et al 2011). To date, only a few preclinical studies have explored the efficacy of antiapoptotic protein antagonists in restoring sensitivity in AMCD-resistant cancer cell lines with deregulated apoptosis.…”
Section: Mechanisms Of Acquired Resistance To Amcdsmentioning
confidence: 99%